KOMUNIKASI VERBAL (Konsep Mendengarkan dalam al-Quran) - Zainab, Siti (Jurnal Studi Agama dan Masyarakat, 2014)
The study examines the verbal communication especially it is related to listening in the Qurâan. The problems of the study are: 1) What are terms that are related to listening? 2) What are the Qurâanic concepts related to effective listening? The study is pure library research with tafsir maudhuâiÂ  so that main source of data is the Qurâan, muâjam Li alfafadz al-qurâan, tafsir books and other books related to verbal communication. Â In analyzing the data, the content analysis is used. The results of the study indicate that: Qurâanic terms about listening are not only something to do with physical perception to grasp the sound but also from all the verses, the majority is related to the ability to comprehend and obey to messages being delivered. In the Qurâan, listening effective implies that there should be concrete action to messages being accepted because good listeners tend to be more related to obedience. In order to listen effectively, it is not only with wish and desire to listen to the content of the message but the most important thing is the effort to understand and practice the messages.Â